Monoclonal antibodies against recombinant GAPDH of Edwardsiella tarda reveal the conserved nature of the protein. Issue 4 (4th July 2017) - Banu, Husne; Anand, Deepika; Bedekar, Megha K; Rajendran, K. V; Makesh, M.
ABSTRACT: The outer membrane protein, encoded by glyceraldehyde-3-phosphate dehydrogenase (GAPDH) gene, of Edwardsiella tarda is a highly conserved immunogenic protein. The GAPDH was cloned and expressed in Escherichia coli . The purified protein was used to produce mouse monoclonal antibodies (MAbs). Four stable hybridomas producing MAbs (3G12, 4E9, 5A11 and 9G1) against rGAPDH were obtained. The heavy chains of antibodies produced by the hybridomas were of the isotypes IgG1 and IgM. Cross reactivity of MAbs (3G12 and 9G1) was observed with GAPDH of Aeromonas hydrophila and Micrococcus luteus . MAbs 3G12 and 4E9 reacted with Vibrio cholerae, Salmonella enterica and Penaeus monodon tissues but not with vertebrate GAPDH. None of the MAbs reacted with Staphylococcus aureus . The results indicate that the level of conservation of GAPDH is high among evolutionarily close species. The MAbs developed will be a useful tool to study the evolutionarily conserved and functionally diverse GAPDH.